High resolution ultrasonography of thyroid nodules: can ultrasonographic assessment obviate the need for invasive aspiration cytology in ultrasonographically benign lesions? - Shadab Maqsood; Inzimam Wani; Omair Shah; Tariq Gojwari; Zubaida Rasool; Bashir Laway; Shujaut Farooq (Universitas Gadjah Mada, 2023)
The use of high-resolution ultrasound (HRUS) thyroid imaging has resulted in a significant revolution in the treatment of thyroid nodules. The enigma of thyroid nodules has been a blind spot for radiologists for a long period. Reporting a thyroid nodule as benign or malignant is quite difficult and many times not accurate. The American Collage of Radiology-Thyroid Imaging Reporting and Data System (ACR-TIRADS) 2017 classification has solved this problem to a large extent. However, the classification needed pathological confirmation for it to be highly accurate. We compared our HRUS-based TIRADS labeling of thyroid nodules with thyroid cytopathology using revised Bethesda classification system. Patients detected with thyroid nodules by HRUS were categorized using ACR-TIRADS and further were taken for fine needle aspiration cytology (FNAC) in our department. The pathological results were compared with the initial TIRADS category of the nodule and the effectiveness of the TIRADS classification in categorizing nodules into benign and malignant was assessed using various statistical variables. The initial USG and the FNAC were performed by a single radiologist with over 10 years of experience. A total of 201 patients underwent HRUS followed by FNAC after obtaining written consent in our department. The thyroid nodules labeled as true benign on ACR-TIRADS (TIRADS 2) were all true benign on Bethesda cytopathology (less than Bethesda III), confirming the high accuracy of HRUS. The diagnostic accuracy of HRUS in cases of ACR-TIRADS 3 nodules was approximately 90.6% with an error rate of 9.4%. Nodules labeled as ACR-TIRADS 4 and 5 had error rates of 47% and 10% in labeling nodules as malignant. The ultrasound-based ACR-TIRADS system can accurately predict the likelihood of specific nodules being benign. There is a strong concordance between Bethesda cytology and ACR-TIRADS classification, particularly for benign nodules. In resource-constrained system like ours, patients with TIRADS 2 and 3 nodules can be safely followed obviating the need for an invasive procedure like FNAC.